PELATIHAN KONSELOR PMBA (PEMBERIAN MAKAN BAYI DAN ANAK) PADA REMAJA PUTRI - Nurul Izzah; Rainer Schumacher Rafael Budiawan; Fany Rahmasari; Usman Usman (Media Literasi Indonesia, 2025)
One of the health problems that needs to be watched out for in Indonesia is cases of stunting in children under five. To prevent stunting, one thing that can be done is infant and young child feeding (IYCF). The aim of the proposed PKM is to provide education/socialization about stunting, risk factors and prevention and provide IYCF training to groups of young women. IYCF education and training activities were carried out in the Hall of the Watang Bacukiki Village Head Office on July 19 2024, which was attended by the PKM Team from Muhammadiyah University of Parepare and the Watang Bacukiki Youth PKK as partners. Educational material was delivered by the team leader (Nurul Izzah) related to staunting and PMBA. IYCF training material delivered by a member of the PKM team (Fany Rahmasari) includes selecting nutritious food ingredients, safe cooking methods, and an introduction to good eating habits. PMBA also teaches how to recognize signs of adequate nutrition in children, as well as dealing with eating problems such as low appetite or food allergies. The conclusion of the activity is that this educational activity can increase the knowledge and understanding of partner group members in efforts to prevent stunting as well as improve the skills of partner group members in providing information to pregnant women so that they can provide IYCF according to their age so that the nutritional needs of babies and children can be met